Research on the new mechanism and path of delayed retirement affecting the birth rate - Jinmeng, Zhang; Guan, Guofeng; Guan, Jie (Frontiers in Public Health, 2025)
This paper incorporates time resource spent on caregiving, economic resource spent on caregiving, and delayed retirement into an overlapping generations (OLG) model to examine how delayed retirement affects the birth rate and through which pathways. It further measures and analyzes the impact of delayed retirement on the proportion of economic resource spent on caregiving relative to the total economic cost of raising children, as well as the joint effects on social welfare. The findings show that delayed retirement leads to a decline in the birth rate. Although it increases older participation in economic resource spent on caregiving, the positive effect of raising its proportion in the total cost of childrearing is outweighed by the negative effect of reduced time resource spent on caregiving. Numerical simulations reveal a reverse relationship between time resource spent on caregiving and economic resource spent on caregiving under the maximization of social welfare. Delayed retirement increases older participation in economic resource spent on caregiving and improves social welfare to some extent. Overall, social welfare rises because the positive effect of increased economic support outweighs the negative effect associated with delayed retirement. Therefore, it is necessary to promote the gradual implementation of delayed retirement and complement it with measures that reduce the time cost of childrearing for young parents so as to support higher fertility.